STUDY OF AMYLASE ACTIVITY IN MUDSKIPPER PERlOPHTHALMUS KOELREUTERI (PALLAS) - Dhage, K P; Mohamed, O M M J (Indian Journal of Fisheries, 2011)
The diversity in the feeding habits is reflected in the structural adaptations in the alimentary tract. This is further elucidated by the morphological and physiological adaptations. In physiological work, the study of the digestive enzymes shows the correlation with the feeding h(lbits and anatomical features. In the piscicultural practioes therefore, such a study of the digestive enzymes, would be useful in understanding the adjustment of the feed of fishes